Bean moisture diffusivity and dryng kinetics: a comparison of the liquid diffusion model when taking into account and neglecting grain shrinkage - Resende, O.=700 1 Correa, P.C.; Jaren, C.; Moure, A.J.
(Es, En)
ilus., 22 ref.
Keywords: PHASEOLUS VULGARIS; MODELOS MATEMATICOS; DIFUSION; GRANOS; SECADO; HUMEDAD; GRAVIMETRIA; TECNICAS ANALITICAS; ESPAÑA; COEFICIENTE DE DIFUSION